2013
DOI: 10.1002/ctpp.201300032
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Field Emission Effect in the Breakdown Mechanism of Direct‐Current Helium Discharges in Micrometer Gaps

Abstract: This paper contains results of experimental studies of the direct current breakdown voltage curves and voltampere characteristics of discharges generated in a system consisting of two plane-parallel tungsten and molybdenum electrodes at separations from 100 μm to 1 μm. The measurements were performed in the pressure range from 22.5 Torr to 738 Torr. The results are presented in the form of Paschen curves. Based on the measured breakdown voltage curves, the effective yields have been estimated in the case of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…There has been considerable research on the gas breakdown mechanism and validity of the Paschen law for a wide range of driving frequencies [11][12][13][14] and gap distances [15,16]. Such fundamental research is essential because understanding of the breakdown process at different conditions is useful not only for development of efficient plasma source devices but also for controlling the plasma parameters in individual applications.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable research on the gas breakdown mechanism and validity of the Paschen law for a wide range of driving frequencies [11][12][13][14] and gap distances [15,16]. Such fundamental research is essential because understanding of the breakdown process at different conditions is useful not only for development of efficient plasma source devices but also for controlling the plasma parameters in individual applications.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed the deviation of the breakdown voltage curve under micro-gap from the traditional Paschen curve to the field emission which was caused by the strong field strength. 18) Semnani et al realized the quantification of each discharge mechanism in the discharge process by numerical simulation under different gas environments. They estimated the contribution ratio of the three discharge mechanisms to the prebreakdown current and concluded that the gas discharge breakdown under small electrode gaps was dominated by field emission.…”
Section: Introductionmentioning
confidence: 99%